Mitochondrial DNA and anti-mitochondrial antibodies in serum of autistic children. - Zhang, Bodi.; Angelidou, Asimenia.; Alysandratos, Konstantinos-Dionysios.; Vasiadi, Magdalini.; Francis, Konstantinos.; Asadi, Shahrzad.; Theoharides, Athanasios.; Sideri, Kyriaki.; Lykouras, Lefteris.; Kalogeromitros, Dimitrios.; Theoharides, Theoharis C. (2016)
Abstract: Autism spectrum disorders (ASD) are neurodevelopmental disorders characterized by difficulties in communication, cognitive and learning deficits, as well as stereotypic behaviors. For the majority of cases there are no reliable biomarkers or distinct pathogenesis. However, increasing evidence indicates ASD may be associated with some immune dysregulation, and may have a neuroimmune component. We recently showed that the peptide neurotensin (NT) is increased in autistic children. We now show that NT induces release of extracellular mitochondrial DNA (mtDNA) that could act as "autoimmune" trigger. We further show that serum from young autistic patients contains mtDNA (n = 20; cytochrome B, p = 0.0002 and 7S, p = 0.006), and anti-mitochondrial antibody Type 2 (n = 14; p = 0.001) as compared to normally developing, unrelated controls (n = 12). Extracellular blood mtDNA and other components may characterize an autistic endophenotype and may contribute to its pathogenesis by activating autoimmune responses.; Springer Open.